2023
DOI: 10.1007/s12630-023-02534-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparaison du dispositif Vie Scope® et de la vidéolaryngoscopie pour la prise en charge de voies aériennes difficiles anticipées : une étude randomisée contrôlée

Abstract: Purpose The management of patients with an anticipated difficult airway remains challenging. We evaluated laryngeal visualization with the recently introduced Vie Scope® as a straight blade laryngoscope consisting of an illuminated tube necessitating bougie-facilitated intubation vs Macintosh videolaryngoscopy. Methods We conducted a prospective randomized controlled noninferiority trial. Patients undergoing elective ear, nose, and throat or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Correct bougie placement may not be verified through the Vie Scope in situations with significantly restricted glottis view through the channel (i.e., grade 2C or worse); 4 , 5 in our previous study, we observed four unintended esophageal intubations in patients with expected difficult airways 2 probably due to bougie misplacement.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Correct bougie placement may not be verified through the Vie Scope in situations with significantly restricted glottis view through the channel (i.e., grade 2C or worse); 4 , 5 in our previous study, we observed four unintended esophageal intubations in patients with expected difficult airways 2 probably due to bougie misplacement.…”
mentioning
confidence: 67%
“…We thank Dr. Henlin et al . 1 for their interest in our work 2 and for sharing their interesting insights into the “parallel intubation technique.” We are pleased that the authors’ experience is consistent with our previously published study results 2 , 3 suggesting that glottis visualization with the Vie Scope ® (Adroit Surgical LLC, Oklahoma City, OK, USA) is superior to direct laryngoscopy and noninferior to Macintosh videolaryngoscopy, despite increased time-to-intubation. 2 , 3 In our opinion, the good visualization achieved with the Vie Scope is primarily due to direct epiglottis lifting, being a key element of straight-blade techniques and also significantly improving the glottis exposure in difficult Macintosh videolaryngoscopy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We thank Bhakta et al 1 for their interest in our work 2 and for emphasizing the importance of the epiglottis–blade interaction in the management of difficult tracheal intubation.…”
mentioning
confidence: 98%